ANALISIS KONTRIBUSI, EFEKTIVITAS DAN PROYEKSI PENDAPATAN PERUSAHAAN DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN SRAGEN TAHUN 2012 – 2016 - Devi Inggarwati, Suharno & Bambang Widarno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
The purpose of this study is to analyze the contribution, effectiveness and projection of company earnings to the local revenue in Sragen regency in 2012 - 2016. This research is a case study conducted in Sragen Regency in 2012 - 2016. Secondary data used in this research comes from BPPKAD Sragen regency, with research object at company area in Sragen regency. Analytical techniques used are contribution analysis, effectiveness analysis and projection analysis. The result of the analysis of the contribution of local company's revenue to the local revenue in Sragen Regency in 2012 - 2016 shows the average contribution rate of 3.31%, this means that the revenue contribution of regional companies to the local revenue is stated to contribute but not maximally because the percentage less than four percent. The effectiveness analysis concludes that the revenue of regional companies in 2012 - 2016 has an average effective rate of 100.49%, it indicates that the revenue of regional companies 2012 - 2016 can be said to be very effective because the percentage is more than one hundred percent. While the analysis of regional revenue trends and local revenue of Sragen regency from 2017 until 2021 has increased.Keywords: contribution, effectiveness, trend, regional company, local original income